2022
DOI: 10.3389/fmolb.2022.890766
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Implications of Ferroptosis in Renal Fibrosis

Abstract: Renal fibrosis is a common feature of chronic kidney disease (CKD), and can lead to the destruction of normal renal structure and loss of kidney function. Little progress has been made in reversing fibrosis in recent years. Ferroptosis is more immunogenic than apoptosis due to the release and activation of damage-related molecular patterns (DAMPs) signals. In this paper, the relationship between renal fibrosis and ferroptosis was reviewed from the perspective of iron metabolism and lipid peroxidation, and some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 293 publications
(336 reference statements)
0
10
0
Order By: Relevance
“…More specifically, increased expression of renal prostaglandin-endoperoxide synthase (Ptgs2) as a putative marker of ferroptosis was observed in the kidneys. Other ferroptosis-related molecules, including GPXs, iron and lipid peroxides have also been demonstrated (Sponsel et al, 1996; Frontiers in Molecular Biosciences frontiersin.org Himmelfarb, 2005;Zhang et al, 2022), corroborating the involvement of ferroptosis in the pathogenesis of renal fibrosis. Transforming growth factor β1 (TGF-β1) was shown to be a key mediator of renal fibrosis (Ikeda et al, 2014).…”
Section: Ferroptosis Regulatory Genes In Chronic Kidney Diseasementioning
confidence: 66%
“…More specifically, increased expression of renal prostaglandin-endoperoxide synthase (Ptgs2) as a putative marker of ferroptosis was observed in the kidneys. Other ferroptosis-related molecules, including GPXs, iron and lipid peroxides have also been demonstrated (Sponsel et al, 1996; Frontiers in Molecular Biosciences frontiersin.org Himmelfarb, 2005;Zhang et al, 2022), corroborating the involvement of ferroptosis in the pathogenesis of renal fibrosis. Transforming growth factor β1 (TGF-β1) was shown to be a key mediator of renal fibrosis (Ikeda et al, 2014).…”
Section: Ferroptosis Regulatory Genes In Chronic Kidney Diseasementioning
confidence: 66%
“…As a significant characteristic of chronic kidney disease (CKD), renal fibrosis can lead to the loss of the damage of kidney structure and function ( 18 ). An increasing health burden is posed by CKD and renal fibrosis, which affect 10% of the world’s population ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an urgent need to understand the mechanisms of fibrosis and develop new therapeutic strategies. Recent in-depth studies on ferroptosis have revealed a growing body of evidence that highlights the crucial role of ferroptosis in the pathophysiological process of fibrosis [93].…”
Section: Fibrosismentioning
confidence: 99%